Engineer-railroader V.A. Sokovich and magazine «Railway business» - R. O. Fesovets (History of science and technology, 2016)
This article contains activity review of the first dean of the Exploitation Faculty of the Moscow Institute of Railroads V.А. Sokovich the author of scientific articles published in the industrial magazine «Zheleznodorozhnoe Delo» in the period from 1924 to 1931.